Gulf Cooperation Council : The Economic Outlook and Policy Challenges in the GCC Countries. (Policy Papers; Policy Paper, 2017)
Global economic activity is gaining momentum. Global growth is forecast at 3.6 percent this year, and 3.7 percent in 2018, compared to 3.2 percent in 2016. Risks around this forecast are broadly balanced in the near term, but are skewed to the downside over the medium term. The more positive global growth environment should support somewhat stronger oil demand. With inflation in advanced countries remaining subdued, monetary policy is expected to remain accommodative. GCC countries are continuing to adjust to lower oil prices. Substantial fiscal consolidation has taken place in most countries, mainly focused on expenditure reduction. This is necessary, but it has weakened non-oil growth. With the pace of fiscal consolidation set to slow, non-oil growth is expected to increase to 2.6 percent this year, from 1.8 percent last year. However, because of lower oil output, overall real GDP growth is projected to slow to 0.5 percent in 2017 from 2.2 percent in 2016. Growth prospects in the medium-term remain subdued amid relatively low oil prices and geopolitical risks. Policymakers have made a strong start in adjusting fiscal policy. While the needed pace of fiscal adjustment varies across countries depending on the fiscal space available, in general countries should continue to focus on recurrent expenditure rationalization, further energy price reforms, increased non-oil revenues, and improved efficiency of capital spending. Fiscal consolidation should be accompanied by a further improvement in fiscal frameworks and institutions. The direction of fiscal policy in the GCC is broadly consistent with these recommendations. Policies should continue to be geared toward managing evolving liquidity situations in the banking system and supporting the private sector's access to funding. While countries have made progress in enhancing their financial policy frameworks, strengthening liquidity forecasting and developing liquidity management instruments will help banks adjust to a tighter liquidity environment. Banks generally remain profitable, well capitalized, and liquid, but with growth expected to remain relatively weak, the monitoring of financial sector vulnerabilities should continue to be enhanced. Diversification and private sector development will be needed to offset lower government spending and ensure stronger, sustainable, and inclusive growth. This will require stepped-up reforms to improve the business climate and reduce the role of the public sector in the economy through privatization and PPPs. Reforms are needed to increase the incentives for nationals to work in the private sector and for private sector firms to hire them. Increasing female participation in the labor market and employment would benefit productivity and growth across the region. Where fiscal space is available, fiscal policy can be used to support the structural reforms needed to boost private sector growth and employment.